Economic influence on rights issue announcement behavior in Malaysia - Salamudin, Norhana; Ariff, Mohamed; Md Nassir, Annuar (Elsevier, 1999)
The negative announcement period return for seasoned equity issues in several developed share markets has been explained as an adverse selection effect to information asymmetry between managers and investors during the expansionary phases of share market cycles. This paper reports a significant positive announcement period return in an emerging share market. The average return during periods of favourable economic conditions is higher than return during unfavourable periods. The term premiums, which decline (rise) during favourable (unfavourable) economic conditions, are correlated with announcement period returns. These findings support the good news hypothesis that the return is positive because investors expect the funds from issues to be used in profitable investment projects in a high growth emerging economy.